Immunosenescence profiles are not associated with muscle strength, physical performance and sarcopenia risk in very old adults: The Newcastle 85+ Study. (September 2020) - Granic, Antoneta; Martin-Ruiz, Carmen; Dodds, Richard M; Robinson, Louise; Spyridopoulos, Ioakim; Kirkwood, Thomas BL; von Zglinicki, Thomas; Sayer, Avan A
Highlights: Immunosenescence has been implicated in several age-related disorders. Little is known about the link between immunosenescence and muscle ageing in very old adults. Immunosenescence profiles were derived by clustering of T-cell senescence biomarkers. T-cell senescence was not associated with 5-year decline in muscle function or risk of sarcopenia. Abstract: Decline in immune system function (immunosenescence) has been implicated in several age-related disorders. However, little is known about whether alteration in T-cell senescence, a process underlying immunological ageing, is related to muscle health in very old adults (aged ≥85 years). Utilising data from the Newcastle 85+ Study, we aimed to (a) derive and characterise immunosenescence profiles by clustering 13 baseline immunosenescence-related biomarkers of lymphocyte compartments in 657 participants; (b) explore the association between the profiles and 5-year change in muscle strength (grip strength) and physical performance (Timed Up-and-Go test), and (c) determine whether immunosenescence profiles predict 3-year incident sarcopenia. Two distinct clusters were identified; Cluster 1 ('Senescent-like phenotype', n = 421), and Cluster 2 ('Less senescent-like phenotype', n = 236) in individuals with complete biomarker data. Although Cluster 1 was characterised by T-cell senescence (e.g., higher frequency of CD4 and CD8 senescence-like effector memory cells), and elements of the immune risk profile (lower CD4/CD8 ratio, CMV+), it was not associated with change in muscle function over time, or with prevalent or incident sarcopenia. Future studies will determine whether more in-depth characterisation or change in T-cell phenotypes predict the decline in muscle health in late adulthood.